Vestibular Function After Cochlear Implantation: A Comparison of Three Types of Electrodes. Issue 10 (December 2016) - Frodlund, Jonas; Harder, Henrik; Mäki-Torkko, Elina; Ledin, Torbjörn
Abstract : Objective: To investigate the vestibular function after cochlear implantation with different types of electrode arrays. Study Design: Retrospective cohort study. Setting: Academic tertiary referral center. Materials and Methods: Forty three adults underwent first cochlear implantation. Three consecutive series of patients: Group 1 (n = 13) implanted with a precurved electrode, Group 2 (n = 15) implanted with a straight electrode, Group 3 (n = 15) implanted with a flexible electrode. Patient's vestibular functions were assessed with pre- and postoperative caloric testing using videonystagmography (VNG). The postoperative reduction of the maximum slow phase velocity (MSPV) in the implanted ear was evaluated. Medical charts were reviewed to evaluate the occurrence of late onset of postoperative vestibular symptoms. Results: Mean reduction of MSPV was 7.6/s (standard deviation [SD] 8.0) in Group 1, 23.1/s (SD 16.6) in Group 2, and 0.1/s (SD 18.5) in Group 3. Significant difference was found between Group 1 and 2 ( p < 0.030) and between Group 2 and 3 ( p < 0.001). Group 2 showed a higher prevalence of late onset of clinical vertigo (28.6%) than Group 1 (7.7%) and 3 (6.7%). Conclusion: In this prospective study, significantly larger reductions of caloric responses were found in subjects implanted with a straight electrode compared with subjects implanted with a precurved or flexible electrode. These findings seem to correlate to a higher prevalence of postoperative vertigo.